2021
DOI: 10.2147/dmso.s299562
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Protects Against High Glucose-Induced Podocyte Injury Possibly via Modulation of Autophagy and PI3K/AKT/mTOR Signaling Pathway Through DNA Methylation

Abstract: Aim: Diabetic nephropathy (DN) is a serious health problem worldwide. Epidermal growth factor (EGF) has suggested as a potential biomarker for the progression of chronic kidney disease. In this study, we examined the effects of EGF on the high glucose (HG)-induced podocyte injury and explored the underlying molecular mechanisms. Methods: The cell proliferation, toxicity, and cell apoptosis of podocytes were determined by CCK-8 assay, lactate dehydrogenase release assay, and flow cytometry, respectively, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“… 38 The EGF was found to protect against high glucose-induced podocyte injury by promoting podocyte proliferation and inhibiting podocyte apoptosis. 39 Exogenous EGF accelerates the regeneration of kidney tubules and the recovery of kidney function in animal models of acute kidney injury. 40 As such, EGF might play a protective role in the reduction of proteinuria by repairing podocytes and tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“… 38 The EGF was found to protect against high glucose-induced podocyte injury by promoting podocyte proliferation and inhibiting podocyte apoptosis. 39 Exogenous EGF accelerates the regeneration of kidney tubules and the recovery of kidney function in animal models of acute kidney injury. 40 As such, EGF might play a protective role in the reduction of proteinuria by repairing podocytes and tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we focused on the role of necroptosis in diabetic nephropathy (DN) and identified EGF, PAG1, and ZFP36 as potential biomarkers associated with necroptosis using the WGCNA algorithm. EGF is mainly generated from the loop of Henle and the renal distal convoluted tubule, and a previous study suggested that EGF may protect against HG-induced podocyte injury by regulating autophagy, promoting cell proliferation, and inhibiting apoptosis [ 29 ]. Tenascin-C exerts a direct stimulatory effect on the epidermal growth factor (EGF) receptor signaling pathway within muscle stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…In proliferative LN, immune complex deposition leads to glomerular visceral epithelial cells (podocytes) damage and proteinuria. Recently, EGF has been shown to promote podocyte proliferation and re-expression of differentiation markers after exposure to high glucose concentrations [ 40 ]. Therefore, EGF could decrease proteinuria in LN by restoring glomerular function through its ability to repair podocytes.…”
Section: Discussionmentioning
confidence: 99%